Penafsiran Interelasi Q.S. Al Baqarah:233 Sebagai Upaya Meningkatkan Kesejahteraan Keluarga: Perspektif Qira’ah Mubadalah - Rafli, Mohammad; Nasrulloh, M; Toha Hidayatullah, M (Indonesian Proceedings and Annual Conference of Islamic Law And Sharia Economic (IPACILSE), 2023)
Family welfare is much influenced by aspects of meeting family needs. Livelihood is one of the keys to achieving this prosperity. Understanding of religious texts is often taken literally without careful and critical interpretation, as a result, men (husbands) only have to understand the subject of breadwinners. Understanding mub is one of the right approaches to understanding these religious texts. The purpose of this study is to understand the interpretation of Q.S al Baqarah: 33 in interrelationship as an effort for family welfare. The method used is literature study with the Qiraah Mubadalah approach and content analysis. The results of this study 1) the obligation to provide a living in a good way which is borne by the husband in Q.S al Baqarah: 233 can also be the obligation of a wife. 2) The wife cannot immediately file for divorce by assuming the obligation to provide maintenance is only borne by the husband and if the husband is unable to provide maintenance due to conditions that are not possible such as illness and so on or if the wife has income above her husband, then the wife is also subject to the obligation to provide maintenance to husband and family in a way that is maruf. Thus family relations will be more prosperous and harmonious because they consider living as a shared responsibility.